Village Fund Management in Democratic Governance Perspective (Case Study of Tlagasana Village, Watukumpul District, Pemalang Regency) - Hesti Widianti; Andri Widianto; Fitri Amaliyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The policy formulation carried out by the Government in the current reform era is very different from the policy formulation process in the New Order era. Currently, society demands a change in the policy formulation system. The formulation of a good public policy must be based on good and democratic governance. The concept of democratic governance has the meaning of public power or in other words, is a form of government where the public are the holders of the highest power; this concept is used as an institutional framework to strengthen village autonomy. However, the reality is that good governance practices in Indonesia are still not maximized with more village fund practices that have not been directed to the public. The purpose of this study is to understand the form and practice of managing village funds and good governance in the process of managing village funds which will be seen from the process of transparency, accountability, and participation. Data collection techniques using observation and interviews. This study uses a qualitative descriptive with a phenomenological approach to describe the application of good governance in managing village funds. The data analysis method used was data reduction, data display, and conclusion verification. The researcher found that the implementation of village fund management in Tlagasana Village was normatively appropriate and quite good, although there were still some weaknesses in its application in the field and the policy implications were not maximized. This study can be used to evaluate good governance implementation, particularly in village government organizations and the administration of village funds.